2021
DOI: 10.1177/21501327211013298
|View full text |Cite
|
Sign up to set email alerts
|

Developing Risk Assessment Criteria and Predicting High- and Low-Dengue Risk Villages for Strengthening Dengue Prevention Activities: Community Participatory Action Research, Thailand

Abstract: Background: Risk assessment criteria for predicting dengue outbreak must be appropriated at village levels. We aimed to develop risk dengue village prediction criteria, predict village dengue risk, and strengthen dengue prevention based on community participation. Methods: This participatory research conducted in Southern Thailand included the following 5 phases: (i) preparing communities in 3 districts; (ii) developing risk dengue village prediction criteria; (iii) applying computer program; (iv) predicting v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…A possible reason could be that, although all VHVs were equally trained regarding the process of the surveillance system, only the head of VHVs and the health care officer received training concerning dengue solutions. Alternatively, dengue risk assessment may be known to all VHVs, but they may not be able to effectively communicate its results [ 25 ]. It is also possible that VHVs from H-RDVs had greater UDS than those from L-RDVs because of differences in factors such as the public health officer's training in PCUs, sex, time of work, and dengue experience in the past 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible reason could be that, although all VHVs were equally trained regarding the process of the surveillance system, only the head of VHVs and the health care officer received training concerning dengue solutions. Alternatively, dengue risk assessment may be known to all VHVs, but they may not be able to effectively communicate its results [ 25 ]. It is also possible that VHVs from H-RDVs had greater UDS than those from L-RDVs because of differences in factors such as the public health officer's training in PCUs, sex, time of work, and dengue experience in the past 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Villages in the district are predicted to be at high and low risk for dengue based on a community participatory action approach. This prediction was divided into three steps [ 24 , 25 ]. Step 1 was to determine the risk of dengue using prediction criteria.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 1. Determine the dengue risk using the dengue risk assessment criteria and the prediction of high/low risk criteria from the study in southern Thailand [12]. Dengue risk refers to an opportunity for dengue to emerge in a region.…”
Section: Development Stepmentioning
confidence: 99%
“…It showed that few SAOs have an understanding of the act, which results in inadequate enforcement [5]. In addition to the participation of the community members in dengue prevention, control activities were conducted by researchers, with supporting funds from outside the community [8][9][10][11][12][13][14]. Furthermore, the knowledge, attitude, practice, and behavior of the stakeholders were found to be crucial for dengue control [15].…”
Section: Introductionmentioning
confidence: 99%